(untitled) (Szociológiai Szemle, 2024)
The objective of our paper is to describe the network of relationships of foreign students studying in our country and to give an explanation to some of its characteristics. The sample consisting of one hundred male students of the Semmelweis University of Medical Sciences, was further divided into five groups of ethnic origin so that comparisons could be made. Our basic hypothesis, according to which the foreign student groups, studying in Hungary are characterised by being closed and segregated, was proved. However, our other assumption that the number and quality of the Hungarian contacts of the subgroups would be markedly differentiated by their cultural and ethnic differences, could not be verified. The surprising result of our survey is that contacts among members of the different subgroups are extremely modest.